Penguatan Literasi Keagamaan Sebagai Sarana Pemberdayaan Sosial Masyarakat Marginal Desa Koto Iman - Yaltavera, Nabila; Kohar, Wakidul; Yudhiani, Walan (Community Development: Jurnal Pengembangan Masyarakat Islam, 2025)
Strengthening Religious Literacy as a Means of Social Empowerment for Marginalized Communities in Koto Iman Village. Marginalized communities in Indonesia often face exclusion in various aspects of life, particularly in accessing education and religious understanding. This condition limits their ability to gain knowledge that could improve their quality of life. One critical yet overlooked aspect is religious literacy, which goes beyond reading sacred texts to include an understanding of religious values that promote social transformation. Strengthening religious literacy can serve as an effective tool for social empowerment by introducing values such as justice, solidarity, and social change tailored to their lived realities. This study explores how religious literacy can be utilized as a means of empowering marginalized communities. Specifically, it analyzes relevant and contextual forms of religious literacy, examines implementation strategies, and identifies the challenges encountered in strengthening religious literacy among marginalized groups. Using a qualitative approach, this research combines literature review and in-depth interviews with religious leaders, community figures, and social institutions engaged in faith-based empowerment. Thematic analysis is employed to identify key themes related to the forms, strategies, and challenges of implementing religious literacy for social empowerment. The findings aim to offer practical recommendations to strengthen religious literacy as a sustainable tool for community empowerment.